Coworker Influence and Labor Mobility: Essays on Turnover, Entrepreneurship and Location Choice in the Danish Maritime Industry - Christine D. Isakson (Copenhagen Business School (CBS), 2013)
It is critically important to understand the connection between social interaction and individual economic choice (Granovetter 2005). This thesis asks the overall question; How do social relations, specifically coworkers, in the organizational context, influence individual economic choice? The three economic outcomes being examined are turnover, entrepreneurship (the choice to start a business or firm) and location choice (the choice of where to live). These three economic choices are linked to social relations in the organizational context by examining different facets of coworker or peer influence. Common to all papers are mechanisms pertaining to communication, knowledge transfer and coworker influence.
hdl:10398/8654
Keywords: 650